The Urgency of Premarital Medical Testing in Islamic Family Law: A Maqasid al-Shari'ah Perspective - Mohammad Amin; Dahlan Tamrin; Sachrawi Hidayat; Syahrasaddin Syahrasaddin; Mohammad Jindan Alfayed Dewa Filhaq; Naufal Rifqi Nasution (Seutia Hukamaa Cendekia, 2026)
Premarital medical testing represents a critical yet underregulated aspect of Islamic family law in Indonesia. This study examines the urgency of premarital medical testing from the perspective of Maqasid al-Shari'ah, addressing three research questions: Why is premarital medical testing necessary? What is the urgency of such testing for prospective spouses? And how does premarital medical testing align with the objectives of Maqasid al-Shari'ah? Using normative juridical methodology grounded in library research, this study analyzes Qur'anic verses, Prophetic traditions, classical fiqh texts, and Indonesian statutory sources. The findings reveal that premarital testing addresses four critical health risks: sexually transmitted infections (HIV/AIDS, syphilis, hepatitis), hereditary conditions (thalassemia 6-10% carrier rate), fertility-related conditions (10-15% couples affected), and maternal-infant mortality factors. The study demonstrates that premarital testing aligns directly with Maqasid al-Shari'ah, primarily serving hifz al-nafs (protection of life) and hifz al-nasl (protection of progeny), categorized at hajiyyat level within daruriyyat objectives. The practice is justified through sadd al-dhara'i' (blocking pathways to harm) and dar' al-mafasid (prevention of harm) principles. Current Indonesian regulation (Joint Instruction No. 02/1989) is inadequate, mandating only TT immunization for females. The study recommends comprehensive national regulation mandating screening for both genders, BPJS Kesehatan integration, training for KUA officials, and adoption of Muslim-majority country models. This research contributes novel insights through daruriyyat-versus-hajiyyat distinction, Indonesian empirical data, and wajib kifayah versus wajib 'ayn mediation.